Coastal Aquifer Management-Monitoring, Modeling, and Case Studies - Cheng, Alexander H.D. (CRC Press, 2009)
Approximately 70% of the world's population lives in coastal areas, and the majority of these people depend on coastal aquifers for freshwater. The fragility of these aquifers and their sensitivity to human activity demand informed, competent management to guarantee their survival. Significant knowledge and new technologies related to the subject have accumulated in the last two decades, and a need has emerged for a comprehensive reference that gathers and disseminates crucial information to engineering practitioners and policymakers.